Front and Back Matter for Volume 2 Issue 1, January 2025 - Trends in General Medicine and Public Health, Svāsthya: (Svāsthya: Trends in General Medicine and Public Health, 2025)
Volume 2, Issue 1, January 2025 This issue consists of 5 articles contributed by 23 authors affiliated with 7 affiliations from two countries, including Indonesia (Universitas Maarif Hasyim Latif, Universitas Negeri Makassar, Universitas Mega Buana Palopo, Universitas Hindu Indonesia, Universitas Udayana), and Ethiopia (Jimma University, Jigjiga University, College of Veterinary Medicine).